Feminisme dalam Perspektif Hak Asasi Manusia dan Hukum Islam - Putri Vianita; Mulyadi; Mohammad Haris Taufiqur Rahman (State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
Abstract: Feminism is an important movement that challenges patriarchal domination and various forms of discrimination against women in social, cultural and religious contexts. This movement fights for gender equality, eliminating male hegemony, and freeing women from gender-based injustice. In the context of human rights and Islam, feminism advocates fair equality and the elimination of discrimination against women, based on the universal values ​​of the Koran and hadith that encourage respect for the dignity of women. The focus of discussion in this research is, what is the concept of feminism?, and secondly, what is the perspective of human rights and Islamic law regarding the concept of feminism? The research method used in this research is a qualitative research method. The implications of this research support social change, inclusive policies, and efforts to achieve a more just society for all individuals, regardless of gender. Keywords: Feminism, Human Rights, Islamic Law Abstrak: Feminisme adalah gerakan penting yang menantang dominasi patriarki dan berbagai bentuk diskriminasi terhadap perempuan dalam konteks sosial, budaya, dan agama. Gerakan ini memperjuangkan kesetaraan gender, menghapuskan hegemoni laki-laki, dan membebaskan perempuan dari ketidakadilan berbasis gender. Dalam konteks hak asasi manusia dan Islam, feminisme mengadvokasi kesetaraan yang adil dan eliminasi diskriminasi terhadap perempuan, didasarkan pada nilai-nilai universal Al-Qur'an dan hadis yang mendorong penghargaan terhadap martabat perempuan. Fokus pembahasan dalam penelitian ini adalah, bagaimana konsep feminisme?, dan kedua bagaimana perspektif hak asasi manusia dan hukum Islam tentang konsep feminisme?. Metode penelitian yang digunakan dalam penelitian ini yakni metode penelitian kualitatif. Implikasi dari penelitian ini mendukung perubahan sosial, kebijakan inklusif, dan upaya mencapai masyarakat yang lebih adil bagi semua individu, tanpa memandang jenis kelamin. Kata Kunci: Feminisme, Hak Asasi Manusia, Hukum Islam